The Phytochemical Rhein Mediates M6A-Independent Suppression of Adipocyte Differentiation - Huang, Linyuan; Zhang, Jun; Zhu, Xinyun; Mi, Xue; Li, Qiujie; Gao, Jing; Zhou, Jianheng; Zhou, Jun; Liu, Xiao-Min (Frontiers in Nutrition, 2021)
Adipogenesis is mediated by complex gene expression networks involving post-transcriptional modifications. The natural compound rhein has been linked to the regulation of adipogenesis, but the underlying regulatory mechanisms remain elusive. Herein, we systematically analyzed the effects of rhein on adipogenesis at both transcriptional and post-transcriptional levels. Rhein remarkably suppresses adipogenesis in stage-specific and dose-dependent manners. Rhein has been identified to inhibit FTO demethylase activity. Surprisingly, side-by-side comparison analysis revealed that rhein treatment and FTO knockdown triggered differential gene regulatory patterns, resulting in impaired adipocyte formation. Specifically, rhein treatment mildly altered the transcriptome with hundreds of genes dysregulated. N6-methyladenosine (m6A) methylome profile showed that, although supply of rhein induced increased m6A levels on a small subset of mRNAs, few of them showed dramatic transcriptional response to this compound. Moreover, the specific rhein-responsive mRNAs, which are linked to mitotic pathway, are barely methylated or contain m6A peaks without response to rhein, suggesting separate regulation of global m6A pattern and adipogenesis mediated by rhein. Further identification of m6A-independent pathways revealed a positive regulator, Reep3, in guidance of adipogenesis. Altogether, our study provides mechanistic view of cellular actions of rhein in modulation of adipogenesis and identifies a potential novel target for obesity therapeutic research.